Separator for lithium ion battery, preparation method and lithium ion battery
Patent Information
- Application Number
- CN202611230498.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-13
AI Technical Summary
本申请中锂离子电池用隔膜通过在基膜表面设置包含碳包覆偏铝酸锂(LiAlO2@C)的功能表层,提升了电池的整体性能与安全性。首先,碳包覆结构有效增强了偏铝酸锂颗粒的化学稳定性,抑制了其在储存和加工过程中过早与环境中微量水分发生水解反应,从而保证了材料在电池组装阶段的完整性与可控性。其次,该功能表层中的纳米级LiAlO2在电池首次充电至特定电位时,可在微量水环境下发生缓慢而可控的水解反应(LiAlO2+ 2H2O→ Li++ OH-+ Al(OH)3),原位释放出活性锂离子,用于补偿SEI膜形成过程中所消耗的锂,从而有效提升电池的首次库伦效率,并为后续循环提供持续的锂补充,延长循环寿命。与此同时,反应生成的OH-使局部环境呈碱性,能够高效中和电解液中危害较大的游离HF酸,减少其对电极材料尤其是负极界面的腐蚀,提升电池的化学稳定性。此外,水解产物Al(OH)3为不溶性沉淀,可在负极界面参与SEI膜的构建,丰富其无机成分,特别是促进致密LiF的形成,进一步增强SEI膜的稳定性和离子导通能力,有利于降低界面阻抗,改善低温性能。更为重要的是,整个补锂、除水、除酸过程是一种自触发、自限性的“自牺牲”机制,仅在电池激活阶段按需响应,避免了传统补锂工艺中因反应剧烈或不可控而导致的产气、热失控等问题,极大提升了电池的安全性与可靠性。综上所述,该隔膜不仅具备功能性补锂能力,还兼具除水、除酸和界面调控等多重作用,从源头上优化了电池内部化学环境,显著提高了锂离子电池的首次效率、循环稳定性和热安全性,尤其适用于高能量密度、长寿命动力电池的应用需求。
Smart Images

Figure CN122907841A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium-ion battery technology, and more specifically, to separators for lithium-ion batteries, preparation methods, and lithium-ion batteries. Background Technology
[0002] The core components of an ion battery include the positive electrode, negative electrode, separator, electrolyte, and structural components. The separator's key function is to isolate the positive and negative electrodes. Its porous structure provides pathways for lithium ions to shuttle between the electrodes and also adsorbs electrolyte, thus ensuring the battery's long-term cycle stability. During the initial charge and discharge cycle, an SEI film forms on the negative electrode surface. This process consumes some lithium ions, resulting in a low initial coulombic efficiency. While this phenomenon has a positive effect on subsequent cycle stability, it irreversibly loses the active lithium source, directly weakening the battery's reversible capacity output capability. Especially with the increasing demand for high energy density, each instance of ineffective lithium resource loss signifies a decrease in overall energy utilization. With the gradual application of high-capacity new negative electrode materials such as silicon-based and lithium metal negative electrodes, their inherently large specific surface area and strong reducing properties further exacerbate the excessive growth of the SEI film and lithium consumption, making the initial efficiency problem increasingly prominent. When battery modules are used in groups, the slight initial efficiency differences between individual cells are amplified during cycling, affecting consistency management and the accuracy of system lifespan prediction. Furthermore, in various application scenarios such as consumer electronics, electric vehicles, and energy storage systems, user demands for driving range, fast charging response, and service life are continuously increasing, all of which heavily rely on the effective utilization of initially available lithium. Therefore, how to reduce the irreversible consumption of active lithium during the first charge and discharge cycle has become a fundamental and unavoidable issue for improving the overall performance and economics of lithium-ion batteries. This problem not only concerns the efficiency of the electrochemical system but also profoundly impacts the cost-effectiveness and resource sustainability throughout the battery's entire lifecycle.
[0003] Therefore, this application is hereby submitted. Summary of the Invention
[0004] The purpose of this application is to provide a separator for lithium-ion batteries, a preparation method thereof, and a lithium-ion battery, which is beneficial to improving the cycle performance of lithium-ion batteries.
[0005] This application is implemented as follows: In a first aspect, this application provides a separator for lithium-ion batteries, including a base film and a functional surface layer disposed on the surface of the base film, wherein the functional surface layer includes carbon-coated lithium aluminate.
[0006] In an optional embodiment, the carbon-coated lithium aluminate includes a lithium aluminate substrate and a carbon coating layer deposited on at least a portion of the surface of the lithium aluminate.
[0007] In an optional embodiment, the D50 of the lithium aluminate substrate is 100~200nm; And / or, the specific surface area of the lithium aluminate matrix is >30 m². 2 / g; And / or, the mass fraction of the carbon coating layer in the carbon-coated lithium aluminate is 1.0~1.5%; And / or, the process gas used to deposit the carbon coating is an acetylene / argon mixture, and the deposition temperature is 400-700℃.
[0008] In an optional embodiment, the carbon-coated lithium aluminate particles are soaked in deionized water for 24 hours and then filtered and dried, with a mass loss of <0.5%. And / or, the carbon-coated lithium aluminate particles are immersed in an electrolyte and a 0.1C current is applied. After 48 hours, the water content of the electrolyte is less than 6 ppm and the HF acid content is less than 12 ppm. The initial components of the electrolyte include 2.5% vinylene carbonate, 0.5% fluoroethylene carbonate, 13.1% LiPF6, 25% ethylene carbonate, 25% methyl ethyl carbonate, and 33.9% dimethyl carbonate.
[0009] In an optional embodiment, the mass fraction of carbon-coated lithium aluminate in the functional surface layer is 50-80 wt%. And / or, the functional surface layer further comprises polyacrylic acid, wherein the mass fraction of the polyacrylic acid in the functional surface layer is 8-12 wt%; And / or, the functional surface layer further includes sodium carboxymethyl cellulose, wherein the mass fraction of sodium carboxymethyl cellulose in the functional surface layer is 10-13 wt%; And / or, the functional surface layer further includes a dispersant, wherein the mass fraction of the dispersant in the functional surface layer is 0.8-1.2 wt%; And / or, the functional surface layer further includes a wetting agent, wherein the mass fraction of the wetting agent in the functional surface layer is 0.05-0.06 wt%; And / or, the functional surface layer also includes boehmite, wherein the mass fraction of boehmite in the functional surface layer is less than or equal to 25 wt%.
[0010] In an optional embodiment, the base film is selected from PE film; And / or, the thickness of the base film is 5-10 μm.
[0011] In an optional implementation, the thickness of the functional surface layer is 1-3 μm.
[0012] Secondly, this application provides a method for preparing a lithium-ion battery separator as described in the foregoing embodiments, comprising coating a slurry containing the raw materials for the lithium-ion battery separator onto the surface of a base film, followed by drying, to obtain the lithium-ion battery separator.
[0013] In an optional embodiment, the slurry further contains water, and the water mass fraction in the slurry is 40-60 wt%.
[0014] Thirdly, this application provides a lithium-ion battery, including the lithium-ion battery separator described in any of the foregoing embodiments.
[0015] Fourthly, this application provides a battery pack including the battery described in the foregoing embodiments.
[0016] Fifthly, this application provides an electrical device, including the battery or battery pack described in the foregoing embodiments.
[0017] This application has the following beneficial effects: In this application, the separator for lithium-ion batteries improves the overall performance and safety of the battery by setting a functional surface layer containing carbon-coated lithium aluminate (LiAlO2@C) on the surface of the base film. First, the carbon coating structure effectively enhances the chemical stability of the lithium aluminate particles, inhibiting premature hydrolysis with trace amounts of moisture in the environment during storage and processing, thus ensuring the integrity and controllability of the material during battery assembly. Second, the nano-sized LiAlO2 in this functional surface layer can undergo a slow and controllable hydrolysis reaction (LiAlO2 + 2H2O → Li) in a trace water environment when the battery is first charged to a specific potential. + + OH - The reaction generates Al(OH)3, which releases active lithium ions in situ to compensate for the lithium consumed during SEI film formation, thereby effectively improving the battery's initial coulombic efficiency and providing continuous lithium replenishment for subsequent cycles, extending cycle life. Simultaneously, the OH- ions generated during the reaction... -By creating an alkaline local environment, this membrane effectively neutralizes harmful free HF acid in the electrolyte, reducing its corrosion of electrode materials, especially the negative electrode interface, and improving the battery's chemical stability. Furthermore, the hydrolysis product Al(OH)3, an insoluble precipitate, can participate in the construction of the SEI film at the negative electrode interface, enriching its inorganic components, particularly promoting the formation of dense LiF, further enhancing the stability and ion conductivity of the SEI film, which helps reduce interfacial impedance and improve low-temperature performance. More importantly, the entire lithium replenishment, water removal, and acid removal process is a self-triggered, self-limiting "self-sacrificing" mechanism, responding only on demand during the battery activation stage. This avoids problems such as gas generation and thermal runaway caused by violent or uncontrollable reactions in traditional lithium replenishment processes, greatly improving battery safety and reliability. In summary, this separator not only possesses functional lithium replenishment capabilities but also performs multiple functions such as water removal, acid removal, and interface regulation, optimizing the internal chemical environment of the battery from the source. This significantly improves the initial efficiency, cycle stability, and thermal safety of lithium-ion batteries, making it particularly suitable for high-energy-density, long-life power battery applications. Attached Figure Description
[0018] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 This is a SEM image of the carbon-coated lithium aluminate prepared in Example 1; Figure 2 A schematic diagram of the structure of the lithium-ion battery provided in this application; Figure 3 This is a schematic diagram of the battery pack provided in this application; Figure 4 A schematic diagram of the electrical device provided in this application.
[0020] Diagram: 100 - Upper casing; 200 - Lithium-ion battery; 300 - Lower casing. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0022] During the initial charge and discharge of an ion battery, a solid electrolyte interphase (SEI) film forms on the surface of the negative electrode. This process inevitably consumes some of the active lithium ions in the system, resulting in a lower initial coulombic efficiency, which in turn affects the battery's energy density and cycle life. To compensate for this lithium loss, researchers have proposed various lithium replenishment technologies, mainly including adding lithium replenishment materials to the positive electrode, pre-lithiation technology of the negative electrode, and introducing lithium replenishment additives through the electrolyte or separator. Positive electrode lithium replenishment materials, such as lithium-rich compounds Li₂NiO₂ and Li₂MnO₃, can release additional lithium ions during charging to compensate for the lithium loss during SEI film formation. However, these materials typically undergo delithiation reactions at higher voltages or temperatures, easily triggering electrolyte oxidation and decomposition, producing gases (such as CO₂ and O₂). This not only affects the stability of the cell structure but may also lead to bulging or even safety risks. Furthermore, the reaction is highly uncontrollable, making it difficult to precisely match the amount of lithium replenishment. Excessive delithiation may also damage the positive electrode structure and reduce cycle life.
[0023] Negative electrode pre-lithiation is a direct and efficient method for lithium replenishment. Common methods include chemical pre-lithiation using lithium metal foil or lithium powder in contact with the negative electrode material, or electrochemical pre-lithiation using an external power source. This method can significantly improve the initial coulombic efficiency, but its operation must be carried out in a strictly inert atmosphere (such as an argon glove box), which places extremely high demands on the production environment and results in high equipment costs. Furthermore, lithium metal is chemically highly reactive and readily reacts violently with moisture and oxygen in the air, posing a risk of combustion or explosion and resulting in poor safety. In addition, the degree of pre-lithiation is difficult to control; localized over-lithiation may lead to lithium dendrite precipitation, increasing the risk of short circuits and limiting its application in large-scale industrial production.
[0024] The third type of lithium replenishment technology involves introducing functional lithium replenishment additives into the battery system, such as by adding compounds that reversibly release lithium to the separator or electrolyte. Although this method is relatively simple, it still faces many challenges. Many lithium replenishment additives themselves are unstable and are prone to side reactions with electrolyte components or trace amounts of moisture during storage or cycling, generating harmful substances such as hydrofluoric acid (HF). HF not only corrodes electrode materials, promotes the dissolution of transition metal ions, and damages the SEI film structure, but also exacerbates electrolyte decomposition, deteriorating the cell's thermal stability and cycle performance.
[0025] However, the above-mentioned lithium replenishment technology does not fully consider the impact of residual moisture in the battery system and lacks a simultaneous water removal function. On the contrary, it may exacerbate the damage caused by moisture due to side reactions.
[0026] Therefore, this application provides a separator for a lithium-ion battery 200, including a base film and a functional surface layer disposed on the surface of the base film, wherein the functional surface layer includes carbon-coated lithium aluminate.
[0027] The separator for lithium-ion batteries 200 improves overall battery performance and safety by incorporating a functional surface layer containing carbon-coated lithium aluminate (LiAlO2@C) on the base film surface. First, the carbon coating effectively enhances the chemical stability of the lithium aluminate particles, inhibiting premature hydrolysis with trace amounts of moisture in the environment during storage and processing, thus ensuring the integrity and controllability of the material during battery assembly. Second, the nano-sized LiAlO2 in this functional surface layer undergoes a slow and controllable hydrolysis reaction (LiAlO2 + 2H2O → Li) in a trace water environment when the battery is first charged to a specific potential. + + OH - The reaction generates Al(OH)3, which releases active lithium ions in situ to compensate for the lithium consumed during SEI film formation, thereby effectively improving the battery's initial coulombic efficiency and providing continuous lithium replenishment for subsequent cycles, extending cycle life. Simultaneously, the OH- ions generated during the reaction... - By creating an alkaline local environment, this separator effectively neutralizes harmful free HF acid in the electrolyte, reducing its corrosion of electrode materials, especially the negative electrode interface, and improving the battery's chemical stability. Furthermore, the hydrolysis product Al(OH)3, an insoluble precipitate, can participate in the construction of the SEI film at the negative electrode interface, enriching its inorganic components, particularly promoting the formation of dense LiF, further enhancing the stability and ion conductivity of the SEI film, which helps reduce interfacial impedance and improve low-temperature performance. More importantly, the entire lithium replenishment, water removal, and acid removal process is a self-triggered, self-limiting "self-sacrificing" mechanism, responding only as needed during the battery activation stage. This avoids problems such as gas generation and thermal runaway caused by violent or uncontrollable reactions in traditional lithium replenishment processes, greatly improving battery safety and reliability. In summary, this separator not only possesses functional lithium replenishment capabilities but also performs multiple functions such as water removal, acid removal, and interface regulation, optimizing the internal chemical environment of the battery from the source. This significantly improves the initial efficiency, cycle stability, and thermal safety of the lithium-ion battery 200, making it particularly suitable for high-energy-density, long-life power battery applications.
[0028] It should be noted that the lithium replenishment mechanism of LiAlO2 depends on its slow hydrolysis reaction in a trace water environment (LiAlO2 + 2H2O → Li + + OH -The process of adding Al(OH)3 to the electrode releases lithium ions slowly and is controlled by local moisture content. Incorporating this into the positive and negative electrodes makes it difficult to achieve controllable and uniform lithium replenishment in the complex interfacial environment, potentially leading to localized pH increases, exacerbated side reactions, and compromised electrode structural stability. Furthermore, while carbon coating improves interfacial stability and conductivity to some extent, it doesn't fundamentally alter the non-electrochemically active nature of the particles; excessive introduction reduces the overall energy density of the electrode. In contrast, applying it to the separator surface allows for directional, slow-release lithium replenishment through in-situ hydrolysis during the first charge of the battery, while utilizing the generated OH-... - It neutralizes free HF acid in the electrolyte, inhibits corrosion of aluminum current collectors and dissolution of transition metals, and exerts a synergistic effect of water removal, acid removal and lithium replenishment. Therefore, this application uses carbon-coated lithium aluminate in the separator.
[0029] In an optional embodiment, the carbon-coated lithium aluminate comprises a lithium aluminate substrate and a carbon coating layer deposited on at least a portion of the surface of the lithium aluminate. This application significantly improves the interfacial stability and chemical inertness of the material by constructing a carbon coating layer on the surface of the lithium aluminate substrate. The carbon layer acts as a physical barrier, effectively inhibiting premature reactions between lithium aluminate and moisture or electrolyte components in the environment during storage and early battery operation, thus preventing premature loss of active materials. Simultaneously, the carbon coating layer possesses excellent electronic insulation and ion conductivity, allowing for controlled lithium ion release through hydrolysis at a specific potential at a specific potential without affecting lithium ion transport, achieving controllable lithium replenishment.
[0030] In an optional embodiment, the D50 of the lithium aluminate matrix is 100-200 nm; for example, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, and 200 nm. This particle size range helps to form a uniform and dense functional coating on the functional surface of the separator, which is beneficial to improving the coating's coverage and stability. The nanoscale particle size can achieve a higher specific surface area exposure within a limited thickness, thereby enhancing its contact probability and reactivity with trace amounts of moisture, and promoting its slow hydrolysis reaction (LiAlO2 + 2H2O → Li) in the micro-water environment inside the battery. + + OH - + Al(OH)3), which enhances the overall chemical stability and thermal safety of the battery cell. In addition, a suitable particle size range can avoid the agglomeration problem caused by excessively fine particles, ensure the uniformity of slurry dispersion and the feasibility of coating process, and take into account both material functionality and processing performance.
[0031] And / or, the specific surface area of the lithium aluminate matrix is >30 m². 2 / g, for example 31 m² / g, 35 m² / g, 40 m² / g, 45 m² / g, 50 m² / g, 60 m² / g, 70 m² / g, 80 m² / g, 100 m² / g, and 120 m² / g. A high specific surface area means that the material per unit mass has a larger number of surface active sites, significantly enhancing its interaction with the surrounding medium. In this application, the high specific surface area lithium aluminate matrix can more efficiently undergo a controllable and slow hydrolysis reaction with the trace amounts of water remaining in the battery system, continuously releasing Li... + and OH - This enables stable lithium replenishment and acid removal. This self-sacrificing reaction mechanism helps maintain a stable electrolyte environment during battery cycling, slowing HF accumulation and suppressing the spread of side reactions. Simultaneously, the larger specific surface area enhances reaction kinetics, making the lithium replenishment process more uniform and gentle, avoiding the risk of interfacial instability or lithium dendrite formation that might be caused by sudden large-scale lithium release. Furthermore, the high specific surface area also improves the bonding tightness between the carbon coating layer and the substrate, further enhancing the structural integrity and chemical inertness of the material in the electrolyte environment, preventing excessive reactions or decomposition caused by direct exposure of uncoated areas, thereby ensuring the long-term effectiveness of functional components throughout the cell's lifespan.
[0032] The nanoscale particle size (D50 100~200nm) and high specific surface area (>30m² / g) of the lithium aluminate matrix endow lithium aluminate with a larger reaction contact area, which is beneficial for achieving uniform and slow hydrolysis reaction in a trace water environment and promoting Li + The continuous release of lithium improves lithium replenishment efficiency and utilization.
[0033] In an optional embodiment, the mass fraction of the carbon coating layer in the carbon-coated lithium aluminate is 1.0~1.5%, for example 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, or 1.5%; this balances protection and reactivity, ensuring that the material can still effectively respond to electrochemical signals when needed.
[0034] In an optional embodiment, the process gas used to deposit the carbon coating is an acetylene / argon mixture, and the deposition temperature is 400-700℃, for example, 400℃, 430℃, 470℃, 500℃, 530℃, 570℃, 600℃, 630℃, 670℃, or 700℃.
[0035] Using acetylene / argon gas for vapor deposition at 400-700℃ is beneficial for forming a dense, uniform and firmly attached carbon layer, improving the integrity of the coating, further enhancing the stability of the material in the electrolyte, preventing agglomeration or degradation, and ensuring that it can stably perform the dual functions of water removal and lithium replenishment during the battery's service life.
[0036] For example, acetylene is used as a carbon source in the process gas, and its volume fraction can usually be selected in the range of 5% to 20%, such as 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc., with argon as the balance gas.
[0037] In an optional embodiment, the carbon-coated lithium aluminate particles are soaked in deionized water for 24 hours and then filtered and dried, with a mass loss of <0.5%, for example, 0.05%, 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, or 0.49%. In an optional embodiment, the carbon-coated lithium aluminate particles are immersed in an electrolyte and a 0.1C current is applied. After 48 hours, the water content of the electrolyte is less than 6 ppm, for example, 0.3 ppm, 1 ppm, 1.5 ppm, 2 ppm, 2.5 ppm, 3 ppm, 3.5 ppm, 4 ppm, 4.5 ppm, or 5 ppm, and the HF acid content is less than 12 ppm, for example, 1 ppm, 2 ppm, 3 ppm, 4 ppm, 5 ppm, 6 ppm, 7 ppm, 8 ppm, 9 ppm, 10 ppm, 11 ppm, or 12 ppm. The initial components of the electrolyte include 2.5% vinylene carbonate, 0.5% fluoroethylene carbonate, 13.1% LiPF6, 25% ethylene carbonate, 25% methyl ethyl carbonate, and 33.9% dimethyl carbonate.
[0038] Carbon-coated lithium aluminate meeting the above requirements exhibits excellent environmental stability and reaction controllability. Almost no mass loss occurs in deionized water, indicating that the carbon coating effectively prevents direct contact between lithium aluminate and water, avoiding pre-reactions during storage or processing. Even under simulated battery operating conditions, it can still gradually release OH-. - It consumes water and HF acid, achieving in-situ water removal and acid removal, which helps suppress electrolyte decomposition and side reactions, reduce gas generation, and improve battery safety. The alkaline environment promotes the formation of a stable LiF-rich SEI film at the negative electrode interface, thereby improving interfacial kinetics and cycle life.
[0039] In an optional embodiment, the mass fraction of carbon-coated lithium aluminate in the functional surface layer is 50-80 wt%, for example, 50 wt%, 53 wt%, 57 wt%, 60 wt%, 63 wt%, 67 wt%, 70 wt%, 73 wt%, 77 wt%, or 80 wt%. Within this range, the content of carbon-coated lithium aluminate significantly enhances the functionality of the separator, enabling it to perform both water removal and lithium replenishment. Controlling the mass fraction of carbon-coated lithium aluminate within the range of 50-80 wt% ensures sufficient functional component content for effective lithium replenishment and acid removal, while avoiding problems such as decreased coating mechanical properties, reduced flexibility, or impact on ion transport channels due to excessive addition. Furthermore, an appropriate distribution of functional particles helps maintain the uniformity and density of the coating structure, preventing agglomeration or crack formation, thereby ensuring the reliability of the separator during battery assembly and cycling. This ratio range balances functionality and process compatibility, which is conducive to achieving high-performance, high-stability self-sacrificing functional separators and fully leveraging their synergistic optimization role in battery systems.
[0040] In an optional embodiment, the functional surface layer further comprises polyacrylic acid, wherein the mass fraction of the polyacrylic acid in the functional surface layer is 8-12 wt%, for example 8.0 wt%, 8.4 wt%, 8.9 wt%, 9.3 wt%, 9.8 wt%, 10.2 wt%, 10.7 wt%, 11.1 wt%, 11.6 wt%, or 12.0 wt%. In an optional embodiment, the functional surface layer further includes sodium carboxymethyl cellulose, wherein the mass fraction of sodium carboxymethyl cellulose in the functional surface layer is 10-13 wt%, for example, 10.0 wt%, 10.3 wt%, 10.7 wt%, 11.0 wt%, 11.3 wt%, 11.7 wt%, 12.0 wt%, 12.3 wt%, 12.7 wt%, or 13.0 wt%. In the functional surface layer, polyacrylic acid (PAA) and sodium carboxymethyl cellulose (CMC) act as binders, synergistically enhancing the bonding strength and mechanical flexibility between the coating and the base film, preventing peeling or cracking.
[0041] In an optional embodiment, the functional surface layer further includes a dispersant, wherein the mass fraction of the dispersant in the functional surface layer is 0.8-1.2 wt%, for example, 0.80 wt%, 0.84 wt%, 0.89 wt%, 0.93 wt%, 0.98 wt%, 1.02 wt%, 1.07 wt%, 1.11 wt%, 1.16 wt%, or 1.20 wt%. For example, the dispersant may be selected from at least one of sodium polyacrylate (PAAS), polyethylene glycol (PEG, molecular weight 200-6000), polyvinylpyrrolidone (PVP), polycarboxylate dispersants (such as the BYK series), and sodium dodecylbenzenesulfonate (SDBS).
[0042] In an optional embodiment, the functional surface layer further includes a wetting agent, wherein the mass fraction of the wetting agent in the functional surface layer is 0.05-0.06 wt%, for example, 0.050 wt%, 0.051 wt%, 0.052 wt%, 0.053 wt%, 0.054 wt%, 0.055 wt%, 0.056 wt%, 0.057 wt%, 0.058 wt%, or 0.060 wt%. The dispersant and wetting agent improve the rheological properties of the slurry, achieving uniform coating. For example, the wetting agent may be selected from at least one of polyether-modified siloxanes (such as BYK-349, BYK-333), fatty alcohol polyoxyethylene ethers (AEO series), and alkylphenol polyoxyethylene ethers (such as OP-10).
[0043] In an optional embodiment, the functional surface layer further includes boehmite, wherein the mass fraction of boehmite in the functional surface layer is less than or equal to 25 wt%, for example, 2 wt%, 5 wt%, 7 wt%, 10 wt%, 12 wt%, 15 wt%, 17 wt%, 20 wt%, 22 wt%, or 25 wt%. A small amount of boehmite can improve the heat resistance and electrolyte wettability of the membrane, synergistically enhancing thermal dimensional stability.
[0044] The combination of the above components in the functional surface layer helps to balance the functionality, processability, and long-term stability of the diaphragm.
[0045] In an optional embodiment, the base film is selected from PE film; PE base film has good mechanical strength and ion permeability.
[0046] In an optional embodiment, the thickness of the base film is 5-10 μm, such as 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, 7.5 μm, 8.0 μm, 8.5 μm, 9.0 μm, or 10.0 μm. A moderate thickness can achieve a balance between safety and energy density.
[0047] In an optional embodiment, the functional surface layer has a thickness of 1-3 μm, for example, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.4 μm, 2.6 μm, 3.0 μm, which not only ensures the effective loading of functional particles, but also avoids excessive increase of internal resistance or impact on battery assembly.
[0048] The embodiments of the present application further provide a method for preparing the separator for the lithium ion battery 200 according to the foregoing embodiments, which comprises coating a slurry containing the raw materials of the separator for the lithium ion battery 200 on the surface of a base film, followed by drying to obtain the separator for the lithium ion battery 200.
[0049] Exemplarily, the specific manner of slurry coating may adopt one or more of micro-gravure coating, gravure coating, slot-die extrusion coating, transfer coating, dip coating, spray coating, blade coating, and reverse roll coating.
[0050] In an optional embodiment, the slurry further contains water, and the mass fraction of water in the slurry is 40-60 wt%, for example, 40 wt%, 42 wt%, 45 wt%, 47 wt%, 49 wt%, 51 wt%, 53 wt%, 56 wt%, 58 wt%, 60 wt%. During the slurry preparation process, the presence of water as a solvent can effectively disperse components such as LiAlO2@C particles, PAA, CMC, dispersant, wetting agent and boehmite, ensure uniform mixing of various materials, and form a stable slurry system.
[0051] Exemplarily, the method for preparing the separator for the lithium ion battery 200 includes the following steps: 1. LiAlO2 (D50 100~200 nm, specific surface area >30 m 2 / g) is placed in a vapor deposition chamber, a acetylene / argon mixed gas is introduced, and LiAlO2@C particles are obtained under high temperature heating conditions. A stability test is performed on the prepared LiAlO2@C particles, and those meeting the following conditions are qualified: ① The LiAlO2@C particles are immersed in deionized water for 24 h, then filtered and dried, with a mass loss of <0.5%, ② The LiAlO2@C particles are immersed in an electrolyte containing 2.5% VC, 0.5% FEC, 13.1% LiPF6, 25% EC, 25% EMC, 33.9% DMC, and a current of 0.1C is applied. After 48 h, the moisture content is significantly reduced from the initial 20 ppm to 1 ppm, and the HF acid content is significantly reduced from the initial 50 ppm to 2 ppm.
[0052] 2. The LiAlO2@C particles obtained in step 1 are stirred with PAA, CMC, dispersant, wetting agent, boehmite and deionized water to obtain slurry A.
[0053] 3. The slurry A from step 2 is coated onto the surface of the base film using a gravure roller, and then dried to obtain a self-sacrificing water removal and lithium replenishment diaphragm.
[0054] This application also provides a lithium-ion battery 200, including the separator for the lithium-ion battery 200 described in any of the foregoing embodiments.
[0055] This application does not impose any particular limitation on the shape of the battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 2 This is a square-structured battery as an example. It is understood that the layout of the terminals (or electrode terminals) is not limited to the same-side positive and negative terminals shown in the figure, and they can also be arranged at two opposite ends of the battery. This application does not limit this.
[0056] In some embodiments, the battery includes a casing, within which electrode assemblies are encapsulated. The battery may contain one or more electrode assemblies, which can be selected by those skilled in the art according to specific practical needs.
[0057] This application also provides a battery pack including the battery described in the foregoing embodiments.
[0058] In some implementations, the battery pack may contain one or more battery modules, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery pack.
[0059] Figure 3 An exemplary structure of a battery pack is shown. Figure 3 As shown, the battery pack includes a housing and multiple battery modules disposed within the housing. The housing includes a lower housing 300 and an upper housing 100, with the upper housing 100 covering the lower housing 300 and together forming a closed space to accommodate the battery modules. The multiple battery modules can be arranged in any manner within the housing.
[0060] This application also provides an electrical device, including the battery or battery pack described in the foregoing embodiments.
[0061] The battery or battery pack can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include mobile devices (typically mobile phones, laptops, etc.), electric vehicles (typically pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, or energy storage systems, etc.
[0062] Figure 4This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.
[0063] The features and performance of this application will be further described in detail below with reference to the embodiments.
[0064] Example 1 This embodiment provides a method for preparing a self-sacrificing dehydration and lithium replenishment separator for lithium-ion batteries, specifically including the following steps: 1. LiAlO2 (D50 150nm, specific surface area 60m²) 2 / g) was placed in a vapor deposition chamber, and an acetylene / argon mixture was introduced. The mixture was heated to 500℃ to obtain LiAlO2@C particles. SEM images are shown below. Figure 1 As shown, the mass fraction of the carbon coating layer in the LiAlO2@C particles is 1.2%. Stability test of LiAlO2@C particles: ① After soaking the LiAlO2@C particles in deionized water for 24 hours, they were filtered and dried; the mass loss was <0.5%. ② After soaking the LiAlO2@C particles in an electrolyte containing 2.5% VC, 0.5% FEC, 13.1% LiPF6, 25% EC, 25% EMC, and 33.9% DMC, and applying a 0.1C current, the moisture content decreased from 20 ppm to 5 ppm and the HF acid content decreased from 50 ppm to 10 ppm after 48 hours.
[0065] 2. The LiAlO2@C particles from step 1 are mixed with PAA, CMC, dispersant polyacrylamide, wetting agent alkylphenol polyoxyethylene ether, boehmite, and deionized water in a mass fraction of 25%:5%:6%:0.5%:0.03%:10%:53.47% to obtain slurry A.
[0066] 3. The slurry A from step 2 is coated onto the surface of a 7μm PE base film using a gravure roller, with a coating thickness of 2mm. Then, it is dried to obtain a separator with self-sacrificing water removal and lithium replenishment functions.
[0067] Example 2 This embodiment provides a method for preparing a self-sacrificing dehydration and lithium replenishment separator for lithium-ion batteries 200, specifically including the following steps: 1. LiAlO2 (D50 150nm, specific surface area 60m²) 2LiAlO2@C particles were obtained by placing the carbon coating layer in a vapor deposition chamber, introducing an acetylene / argon mixture, and heating at 650℃. The mass fraction of the carbon coating layer in the LiAlO2@C particles was 1.2%. Stability tests of LiAlO2@C particles: ① After soaking the LiAlO2@C particles in deionized water for 24 hours, they were filtered and dried, with a mass loss of <0.5%. ② After soaking the LiAlO2@C particles in an electrolyte containing 2.5% VC, 0.5% FEC, 13.1% LiPF6, 25% EC, 25% EMC, and 33.9% DMC and applying a 0.1C current, the moisture content decreased from 20 ppm to 1 ppm and the HF acid content decreased from 50 ppm to 2 ppm after 48 hours.
[0068] 2. The LiAlO2@C particles from step 1 are mixed with PAA, CMC, dispersant polyacrylamide, wetting agent alkylphenol polyoxyethylene ether, boehmite, and deionized water in a mass fraction of 25%:5%:6%:0.5%:0.03%:10%:53.47% to obtain slurry A.
[0069] 3. The slurry A from step 2 is coated onto the surface of a 7μm PE base film using a gravure roller, with a coating thickness of 2mm. Then, it is dried to obtain a separator with self-sacrificing water removal and lithium replenishment functions.
[0070] Example 3 This embodiment provides a method for preparing a self-sacrificing dehydration and lithium replenishment separator for lithium-ion batteries, specifically including the following steps: 1. LiAlO2 (D50 150nm, specific surface area 60m²) 2 LiAlO2@C particles were obtained by placing the carbon coating layer in a vapor deposition chamber, introducing an acetylene / argon mixture, and heating at 650℃. The mass fraction of the carbon coating layer in the LiAlO2@C particles was 1.2%. Stability tests of LiAlO2@C particles: ① After soaking the LiAlO2@C particles in deionized water for 24 hours, they were filtered and dried, with a mass loss of <0.5%. ② After soaking the LiAlO2@C particles in an electrolyte containing 2.5% VC, 0.5% FEC, 13.1% LiPF6, 25% EC, 25% EMC, and 33.9% DMC and applying a 0.1C current, the moisture content decreased from 20 ppm to 1 ppm and the HF acid content decreased from 50 ppm to 2 ppm after 48 hours.
[0071] 2. The LiAlO2@C particles from step 1 are mixed with PAA, CMC, dispersant polyacrylamide, wetting agent alkylphenol polyoxyethylene ether, boehmite, and deionized water in a mass fraction of 35%:5%:6%:0.5%:0.03%:0%:53.47% to obtain slurry A.
[0072] 3. The slurry A from step 2 is coated onto the surface of a 7μm PE base film using a gravure roller, with a coating thickness of 2mm. Then, it is dried to obtain a separator with self-sacrificing water removal and lithium replenishment functions.
[0073] Example 4 This embodiment provides a method for preparing a self-sacrificing dehydration and lithium replenishment separator for lithium-ion batteries, specifically including the following steps: 1. LiAlO2 (D50 150nm, specific surface area 60m²) 2 LiAlO2@C particles were obtained by placing the carbon coating layer in a vapor deposition chamber, introducing an acetylene / argon mixture, and heating at 650℃. The mass fraction of the carbon coating layer in the LiAlO2@C particles was 1.2%. Stability tests of LiAlO2@C particles: ① After soaking the LiAlO2@C particles in deionized water for 24 hours, they were filtered and dried, with a mass loss of <0.5%. ② After soaking the LiAlO2@C particles in an electrolyte containing 2.5% VC, 0.5% FEC, 13.1% LiPF6, 25% EC, 25% EMC, and 33.9% DMC and applying a 0.1C current, the moisture content decreased from 20 ppm to 1 ppm and the HF acid content decreased from 50 ppm to 2 ppm after 48 hours.
[0074] 2. The LiAlO2@C particles from step 1 are mixed with PAA, CMC, dispersant polyacrylamide, wetting agent alkylphenol polyoxyethylene ether, and deionized water in a mass fraction of 45%:5%:6%:0.5%:0.03%:43.47% to obtain slurry A.
[0075] 3. The slurry A from step 2 is coated onto the surface of a 7μm PE base film using a gravure roller, with a coating thickness of 2mm. Then, it is dried to obtain a separator with self-sacrificing water removal and lithium replenishment functions.
[0076] Comparative Example 1 This embodiment provides a method for preparing a separator for lithium-ion batteries, specifically including the following steps: 1. Boehmite particles are mixed with PAA, CMC, dispersant, wetting agent and deionized water in a mass fraction of 35%:5%:6%:0.5%:0.03%:53.47% to obtain slurry A.
[0077] 3. The slurry A from step 2 is coated onto the surface of a 7μm PE base film using a gravure roller, with a coating thickness of 2mm, and then dried to obtain a separator for lithium-ion batteries 200.
[0078] The separators obtained in the above examples and comparative examples were used to prepare lithium-ion batteries 200 with LFP positive electrodes, graphite negative electrodes and lithium hexafluorophosphate electrolyte (wherein, when the separator has a coating on one side, the side with the coating faces the negative electrode); the first-efficiency and cycle performance of lithium-ion batteries 200 were tested at a test temperature of 25°C and a charge / discharge voltage range of 2.0V~3.65V.
[0079] The results of the physicochemical and electrochemical performance tests of the diaphragms in the above embodiments and comparative examples are shown in Table 1.
[0080] Table 1. Performance Comparison of Examples and Comparative Examples
[0081] Example 1 of this application uses carbon-coated lithium aluminate (LiAlO2@C) as the functional component, while Comparative Example 1 uses conventional boehmite. As shown in Table 1, the moisture content of Example 1 is 1100 ppm, significantly lower than the 1200 ppm of Comparative Example 1; simultaneously, its thermal shrinkage rate at 130°C is 1.3%, far lower than the 2.6% of Comparative Example 1, demonstrating better thermal stability. Furthermore, although the initial coulombic efficiency (89%) is slightly lower than that of Comparative Example 1 (90%), the retention rate after 500 cycles reaches 93%, superior to the 92% of the Comparative Example. This indicates that although carbon-coated lithium aluminate participates in a small amount of irreversible reaction in the initial stage, leading to a slight decrease in initial efficiency, its slow release of Li... + This ability helps replenish active lithium and improve cycle life. Simultaneously, LiAlO2 undergoes hydrolysis in trace water environments to generate OH-. - It can neutralize the corrosive HF in the electrolyte, reduce side reactions, and thus improve interface stability and thermal safety.
[0082] The main difference between Example 2 and Example 1 is that the carbon coating process temperature is higher at 650°C. As shown in Table 1, the moisture content in Example 2 is reduced to 1000 ppm, thermal shrinkage is further reduced to 1.2%, and cycle retention is improved to 95%. This optimization may stem from the higher deposition temperature enhancing the density and uniformity of the carbon layer, improving the chemical stability of the LiAlO2 particles, reducing pre-reactions during storage and processing, and allowing for more controllable release of Li during battery cycling. + and OH - This allows for more effective removal of moisture and HF acid, enhancing the stability of the SEI membrane and ultimately improving cycle performance and thermal dimensional stability.
[0083] Example 3, while maintaining the same carbon coating process as Example 1, increased the content of carbon-coated lithium aluminate to 35% and completely removed boehmite. Its moisture content was further reduced to 900 ppm, the thermal shrinkage rate decreased to 0.6%, and the cycle retention rate significantly increased to 98%. This indicates that increasing the proportion of the active lithium-replenishing component, lithium aluminate, enhances both dehydration and lithium replenishment functions, while removing the inert filler boehmite improves the effective contact and reaction efficiency of the functional components. A higher LiAlO2 content means more Li... + It can continuously release lithium to compensate for lithium loss during cycling, while continuously neutralizing HF, inhibiting electrolyte decomposition and electrode corrosion, thereby significantly extending battery life.
[0084] Example 4 further increased the carbon-coated lithium aluminate content to 45%, but the cycle retention rate decreased to 80%, indicating that an excessively high proportion of functional components may damage the mechanical integrity of the coating or affect the ion transport pathway. High concentrations increase the risk of particle agglomeration, potentially leading to poor coating uniformity, increased interfacial impedance, and even localized lithium plating, accelerating capacity decay. Furthermore, excessive hydrolysis may rapidly release OH- in a short period. - Disrupting the electrolyte balance is detrimental to the formation of a stable SEI film.
[0085] In summary, introducing carbon-coated lithium aluminate as a self-sacrificing functional material can achieve multiple functions such as in-situ water removal, HF removal, and lithium replenishment without affecting the basic separator performance. Appropriately increasing its content and optimizing the carbon coating process can significantly improve the battery's cycle stability and thermal safety; however, the addition ratio needs to be controlled to avoid negative impacts. Overall, this application overcomes the shortcomings of traditional separators in dealing with moisture and lithium loss, providing an effective solution for high-safety, long-life lithium-ion batteries.
[0086] In summary, this application introduces carbon-coated lithium aluminate into the functional surface layer of the separator for lithium-ion batteries 200. The lithium aluminate matrix, acting as a self-sacrificing functional material, can slowly hydrolyze during battery cycling, continuously consuming trace amounts of water and free HF in the electrolyte. This effectively inhibits HF corrosion of the positive electrode material and the dissolution of transition metal ions. Simultaneously, the released lithium ions replenish the active lithium loss, improving cycle life, and the generated lithium fluoride helps form a stable negative electrode SEI film. The carbon coating layer provides a physical protective barrier for the lithium aluminate matrix, preventing premature hydrolysis during slurry preparation, coating, and storage, ensuring the functional components effectively remove water and acid during battery service. Furthermore, the carbon layer imparts good electronic conductivity to the coating, reducing interfacial impedance between the separator and electrodes, minimizing battery polarization, and improving rate performance. In addition, as a ceramic coating component, carbon-coated lithium aluminate effectively improves the separator's heat shrinkage resistance and dimensional stability, reducing the risk of thermal runaway, thereby comprehensively improving the safety and overall electrical performance of the lithium-ion battery 200.
[0087] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A separator for lithium-ion batteries, characterized in that, It includes a base film and a functional surface layer disposed on the surface of the base film, the functional surface layer including carbon-coated lithium aluminate.
2. The separator for lithium-ion batteries according to claim 1, characterized in that, The carbon-coated lithium aluminate includes a lithium aluminate matrix and a carbon coating layer deposited on at least a portion of the surface of the lithium aluminate matrix.
3. The separator for lithium-ion batteries according to claim 2, characterized in that, The D50 of the lithium aluminate matrix is 100~200nm; And / or, the specific surface area of the lithium aluminate matrix is >30 m². 2 / g; And / or, the mass fraction of the carbon coating layer in the carbon-coated lithium aluminate is 1.0~1.5%; And / or, the process gas used to deposit the carbon coating is an acetylene / argon mixture, and the deposition temperature is 400-700℃; And / or, the carbon-coated lithium aluminate particles are soaked in deionized water for 24 hours and then filtered and dried, with a mass loss of <0.5%; And / or, the carbon-coated lithium aluminate particles are immersed in an electrolyte and a 0.1C current is applied. After 48 hours, the water content of the electrolyte is less than 6 ppm and the HF acid content is less than 12 ppm. The initial components of the electrolyte include 2.5% vinylene carbonate, 0.5% fluoroethylene carbonate, 13.1% LiPF6, 25% ethylene carbonate, 25% methyl ethyl carbonate, and 33.9% dimethyl carbonate.
4. The separator for lithium-ion batteries according to claim 1, characterized in that, The mass fraction of carbon-coated lithium aluminate in the functional surface layer is 50-80 wt%. And / or, the functional surface layer further comprises polyacrylic acid, wherein the mass fraction of the polyacrylic acid in the functional surface layer is 8-12 wt%; And / or, the functional surface layer further includes sodium carboxymethyl cellulose, wherein the mass fraction of sodium carboxymethyl cellulose in the functional surface layer is 10-13 wt%; And / or, the functional surface layer further includes a dispersant, wherein the mass fraction of the dispersant in the functional surface layer is 0.8-1.2 wt%; And / or, the functional surface layer further includes a wetting agent, wherein the mass fraction of the wetting agent in the functional surface layer is 0.05-0.06 wt%; And / or, the functional surface layer also includes boehmite, wherein the mass fraction of boehmite in the functional surface layer is less than or equal to 25 wt%.
5. The separator for lithium-ion batteries according to claim 1, characterized in that, The base film is selected from PE film; And / or, the thickness of the base film is 5-10 μm; And / or, the thickness of the functional surface layer is 1-3 μm.
6. A method for preparing a separator for a lithium-ion battery according to any one of claims 1-5, characterized in that, The process involves coating a slurry containing the raw materials for the lithium-ion battery separator onto the surface of a base film, followed by drying, to obtain the lithium-ion battery separator.
7. The method for preparing a separator for lithium-ion batteries according to claim 6, characterized in that, The slurry also contains water, and the water content in the slurry is 40-60 wt%.
8. A lithium-ion battery, characterized in that, Includes the separator for lithium-ion batteries as described in any one of claims 1-5.
9. A battery pack, characterized in that, Including the lithium-ion battery as described in claim 8.
10. An electrical device, characterized in that, Includes the lithium-ion battery of claim 8 or the battery pack of claim 9.